Speaking Tests Used by EFL Teachers in Kefamenanu - Thresia Trivict Semiun; Maria Wihelmina Wisrance; Johan Kristian Soleman Missa; Fransiskus Leu (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2023)
Speaking, from the point of view of educational evaluation is considered special because it is interactive and must be measured through direct interaction. This study focuses on the types of speaking tests used by EFL teachers and the challenges faced by EFL teachers in constructing and administering the test. Two EFL teachers from two schools located in Kefamenanu were the subjects of the study. The descriptive qualitative method was employed in conducting this study. The instruments used were the documentation of speaking tests and interviews. Later, the data were analyzed qualitatively. The research results revealed that there were nine types of speaking tests used by the teachers namely oral presentations, free interviews, information transfer questions on a single picture, role play, paraphrasing, giving instructions and directions, conversation, and translation. The challenges faced by the teachers in assessing students’ speaking skills were insufficient time to prepare for the test, the short time to test all students, and no test training provided for the teachers.